Effect of Pea Resistant Starch on Emulsion Gel Properties and in Vitro Digestibility of Myofibrillar Proteins - CHEN Jinyu, HU Fangyang, JI Zhirui, WU Zijian (Shipin Kexue)
In this study, the effects of pea resistant starch type 3 (RS3) at different mass fractions (0%, 2%, 4% and 6%) on the emulsion stability, emulsion gel properties and in vitro digestibility of chicken breast myofibrillar proteins (MP) were analyzed. Fourier transform infrared spectroscopy (FTIR) showed no covalent interaction between MP and pea RS3. The addition of pea RS3 significantly decreased the surface hydrophobicity (P < 0.05) while increasing the fluorescence intensity of MP, indicating enhanced protein-protein interactions. The addition of pea RS3 resulted in improved stability of MP emulsions, as manifested by higher absolute values of zeta potential, smaller droplet sizes and reduced creaming index. These changes promoted the formation of gel networks with improved texture and increased storage modulus (G’), gel strength and water holding capacity (WHC), especially at a pea RS3 concentration of 6%. The chemical force results showed that the addition of pea RS3 led to enhanced hydrophobic interaction and disulfide bonding between MP molecules. Low field-nuclear magnetic resonance (LF-NMR) confirmed that pea RS3 addition facilitated the migration of free water to immobilized water. Furthermore, the incorporation of pea RS3 caused a lower pepsin digestibility without changing the overall in vitro digestibility of MP gels. These results indicated that pea RS3 addition can contribute to the production of high-quality meat products with a low glycemic index without reducing protein digestibility.